β-Adrenergic Inhibition Prevents Action Potential and Calcium Handling Changes during Regional Myocardial Ischemia - Murphy, Shannon R.; Wang, Lianguo; Wang, Zhen; Domondon, Philip; Lang, Di; Habecker, Beth A.; Myles, Rachel C.; Ripplinger, Crystal M. (Frontiers in Physiology, 2017)
β-adrenergic receptor (β-AR) blockers may be administered during acute myocardial infarction, as they reduce energy demand through negative chronotropic and inotropic effects and prevent ischemia-induced arrhythmogenesis. However, the direct effects of β-AR blockers on ventricular electrophysiology and intracellular Ca2+ handling during ischemia remain unknown. Using optical mapping of transmembrane potential (with RH237) and sarcoplasmic reticulum (SR) Ca2+ (with the low-affinity indicator Fluo-5N AM), the effects of 15 min of regional ischemia were assessed in isolated rabbit hearts (n=19). The impact of β-AR inhibition on isolated hearts was assessed by pre-treatment with 100 nM propranolol (Prop) prior to ischemia (n=7). To control for chronotropy and inotropy, hearts were continuously paced at 3.3Hz and contraction was inhibited with 20 μM blebbistatin. Untreated ischemic hearts displayed prototypical shortening of action potential duration (APD80) in the ischemic zone (IZ) compared to the non-ischemic zone (NI) at 10 and 15 min ischemia, whereas APD shortening was prevented with Prop. Untreated ischemic hearts also displayed significant changes in SR Ca2+ handling in the IZ, including prolongation of SR Ca2+ reuptake and SR Ca2+ alternans, which were prevented with Prop pre-treatment. At 5 min ischemia, Prop pre-treated hearts also showed larger SR Ca2+ release amplitude in the IZ compared to untreated hearts. These results suggest that even when controlling for chronotropic and inotropic effects, β-AR inhibition has a favorable effect during acute regional ischemia via direct effects on APD and Ca2+ handling.